Radial approach is better than the femoral one in anomalous high RCA take-off from the left-anterior part of the ascending aorta - Abbasov, Eyvaz (J Cardiol Cases, 2013)
An anomalous right coronary artery (RCA) with a high anterior take-off from ascending aorta is an uncommon and technically challenging vessel to cannulate. There are only a few reports in the literature describing this anomaly. Some of them consider it as a “very rare” or even “extremely rare” anomaly. Here we present a case of anomalous RCA arising from antero-left part of the ascending aorta, 3 cm above sinotubular junction. It was impossible to cannulate the anomalous vessel from the femoral approach by two experienced operators, despite using various catheters. The vessel could easily be engaged from the right radial approach at first attempt. We conclude that in patients with anomalous high RCA take-off from anterior or especially left-anterior part of the ascending aorta, we suggest to switch to the right radial approach and not to lose much time on the femoral one. <Learning objective: The aim of this case is to show superiority of the right radial approach in engaging anomalous RCA coming high from ascending aorta. If you see an anomalous RCA originating highly from anterior or antero-left part of the ascending aorta, do not waste much time trying to engage it from femoral approach, as we did, it's almost impossible. Switch to the right radial approach using simple JR, or even better, LCB catheter, and you will succeed.>